Genetic diversity and antifungal susceptibility patterns of Aspergillus nidulan complex obtained from clinical and environmental sources - Tavakoli, Mahin (2020)
The molecular epidemiology and antifungal susceptibility of Aspergillus nidulans species complex has not been well studied. To evaluate the genetic diversity and antifungal susceptibility patterns of clinical and environmental isolates of A. nidulans complex. Sixty clinical and environmental isolates of Aspergillus section Nidulantes were collected from five countries (Iran, The Netherlands, Spain, Portugal and Greece). The species were molecularly identified by sequencing of β-tubulin gene. The genetic diversity of A nidulans complex isolates (n = 54) was determined with a microsatellite genotyping assay. Antifungal susceptibility profile was determined using EUCAST method. The isolates were classified as A nidulans (46.7%), A spinulosporus (26.6%), A quadrilineatus (10%), A pachycristatus (3.3%), A rugulosus (3.3%), A unguis (5%), A creber, (1.7%), A olivicola (1.7%) and A sydowii (1.7%). Thirty-four sequence types (STs) were identified among the 54 A nidulans complex isolates. A high level of genetic diversity was found among A nidulans sensu stricto strains but low diversity was found among A spinulosporus strains. Amphotericin B showed high MICs to all species. The most active azole was posaconazole (GM = 0.64 mg/L), while itraconazole showed the highest MICs among azoles (GM = 2.95 mg/L). A spinulosporus showed higher MICs than A nidulans sensu stricto for all antifungals except for micafungin and anidulafungin. Interspecies variations may result in differences in antifungal susceptibility patterns and challenge antifungal therapy in infections caused by A nidulans. Differences in the distribution of STs or persistence of multiple STs might be related to the sources of isolation and niche specialisation.